Pain education to prevent chronic low back pain: a study protocol for a randomised controlled trial - Traeger, Adrian C.; Moseley, G. Lorimer; Hübscher, Markus; Lee, Hopin; Skinner, Ian W.; Nicholas, Michael K.; Henschke, Nicholas; Refshauge, Kathryn M.; Blyth, Fiona M.; Main, Chris J.; Hush, Julia M.; Pearce, Garry; et al. (BMJ open, 2014)
Introduction Low back pain (LBP) is the leading cause of disability worldwide. Of those patients who present to primary care with acute LBP, 40% continue to report symptoms 3 months later and develop chronic LBP. Although it is possible to identify these patients early, effective interventions to improve their outcomes are not available. This double-blind (participant/outcome assessor) randomised controlled trial will investigate the efficacy of a brief educational approach to prevent chronic LBP in ‘at-risk’ individuals. - Methods/analysis Participants will be recruited from primary care practices in the Sydney metropolitan area. To be eligible for inclusion participants will be aged 18-75 years, with acute LBP (<4 weeks’ duration) preceded by at least a 1 month pain-free period and at-risk of developing chronic LBP. Potential participants with chronic spinal pain and those with suspected serious spinal pathology will be excluded. Eligible participants who agree to take part will be randomly allocated to receive 2×1 h sessions of pain biology education or 2×1 h sessions of sham education from a specially trained study physiotherapist. The study requires 101 participants per group to detect a 1-point difference in pain intensity 3 months after pain onset. Secondary outcomes include the incidence of chronic LBP, disability, pain intensity, depression, healthcare utilisation, pain attitudes and beliefs, global recovery and recurrence and are measured at 1 week post-intervention, and at 3, 6 and 12 months post LBP onset. - Ethics/dissemination Ethical approval was obtained from the University of New South Wales Human Ethics Committee in June 2013 (ref number HC12664). Outcomes will be disseminated through publication in peer-reviewed journals and presentations at international conference meetings. - Trial registration number https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?ACTRN=12612001180808
Gesehen am 28.09.2020